Standar Pengelolaan Penilaian Peserta Didik di Madarasah Aliyah Ma’arif Balong - Fery Diantoro; Amalia Fitri Ristyana; Eka Aprilia; Fahira Alhamdila Anshori (Southeast Asian Journal of Islamic Education Management, 2024)
Assessment is an activity or process of collecting and processing information so that student learning outcomes can be measured and reviewed. Management of student assessment has standards that must be met by teachers or educators so that the assessment results are objective to measure the level of development and achievement of learning. MA Ma'arif Balong applies standards for managing student assessment with an assessment model that is expected to improve the quality and quality of education. This study was conducted using a descriptive qualitative method, because this study was conducted directly and requires real objects to search for, find and select new knowledge based on several structured theories and principles that are carried out seriously. The purpose of this study is to describe the management model, techniques and factors that influence the assessment. Management of assessment at MA Ma'arif Balong is carried out according to educational assessment standards that are sourced from government regulations on student assessment which are developed and adjusted to the needs of the madrasah. The student assessment model at MA Ma'arif Balong uses authentic assessment, daily test assessment, mid-semester assessment, and final semester assessment. The student assessment technique uses attitude assessment, knowledge assessment and skills assessment. The management of student assessment at MA Ma'arif Balong is influenced by two factors, namely factors from within the test which include test directions or instructions, choice of words on the test instrument, level of test difficulty, inappropriate time and number of questions, and factors from students which consist of the level of student motivation and differences in learning and understanding test.